Technical Writing Curricular Contents and Learner’s Communication Skills Needs: A Congruency Study - Sarcina, Boylie Abenir (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This qualitative-quantitative study was conducted to determine if there is congruency between the existing technical writing contents as taught by English 8 teachers and learners’ communication skills needs as perceived by the colleges served and by industries. As a focal point, congruency indicates whether or not the course • English 8 - as taught, is responsive and tailored to the learners’ needs as perceived by the MSU colleges and the industries based in Iligan City. The data were gathered through a self-made questionnaire distributed to the three groups of respondents drawn from the population by purposive sampling - - three (3) English 8 teachers who taught the course in AY 2006-2007, eighty-six (86) faculty representing the colleges which require English 8, and thirteen (13) industrial and educational employers in Iligan City. The results of this undertaking are hoped to provide useful information to guide the service department, the colleges, the administrators and the curriculum designers in strengthening their programs and linking these to the demands of the world outside.